Necessary condition for the existence of a simple closed geodesic on a regular tetrahedron in the spherical space - Sukhorebska, D.D. (Доповіді НАН України, 2020)
In the spherical space the curvature of the tetrahedron’s faces equals 1, and the curvature of the whole tetrahedron
is concentrated into its vertices and faces. The intrinsic geometry of this tetrahedron depends on the value α
of faces angle, where π/3 < α ≤ 2π/3. The simple (without points of self-intersection) closed geodesic has the type
(p,q) on a tetrahedron, if this geodesic has p points on each of two opposite edges of the tetrahedron, q points on
each of another two opposite edges, and (p+q) points on each edges of the third pair of opposite one. For any coprime
integers (p,q), we present the number αp, q (π/3 < αp, q < 2π/3) such that, on a regular tetrahedron in the
spherical space with the faces angle of value α > αp, q, there is no simple closed geodesic of type (p,q). У сферичному просторі кривина граней тетраедра дорівнює 1, і кривина усього тетраедра зосереджена
як у його вершинах, так і на гранях. Внутрішня геометрія правильного тетраедра у сферичному просторі
залежить від величини α кута його грані, де π/3 < α ≤ 2π/3. Проста (без самоперетину) замкнена геодезична на тетраедрі має тип (p,q), якщо ця геодезична перетинає у p точках одну пару протилежних ребер
тетраедра, у q точках — іншу пару протилежних ребер тетраедра і у (p+q) точках — третю пару протилежних ребер тетраедра. Показано, що для кожної пари взаємно простих натуральних чисел (p,q) існує
таке число αp, q (π/3 < αp, q < 2π/3), що на правильному тетраедрі у сферичному просторі з кутом грані величини α > αp, q не існує простої замкненої геодезичної типу (p,q).